KEEFEKTIFAN MODEL TGT BERBANTU PERMAINAN TEBAK GERAK UNTUK MENINGKATKAN KREATIVITAS PADA PEMBELAJARAN TEMATIK - Wahyuningsih, Tri; Pusari, Ratna Wahyu; Prasetyo, Singgih Adhi (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2020)
In thematic learning the learning independence of students is still lacking and has not optimized the ability to think creatively to improve their creativity due to a lack of confidence so that they have not achieved maximum learning outcomes. Efforts to improve using the Team Games Tournament model are aided by guessing games. The method used in this study is quantitative research. This research is a pre-experimental design with one group pretest-posttest design. The research subjects were fifth grade students of Wonosoco Kudus Elementary School with a total of 20 students. The results of the study showed that learning using the Team Games Tournament model helped the Guess the Motion game to improve the creativity of class V children viewed from the pretest average of 60.55 and the posttest average of 83.35. This is evidenced by the t test of tcount (15,630)> t table (1,684) then H0 is rejected and Ha is accepted. So the conclusion is effective using the Team Games Tournament (TGT) model with the help of Guess the Motion game to Improve Children's Creativity in Thematic Learning.